"Changing the Acquisition Game" Alleviating Unreasonable PM‐SE Constraint Risks. Issue 1 (16th August 2018) - Wasson, Charles; Hahn, Heidi; Neill, Colin J.; Weigel, Allison; Lindeman, Tony
Abstract: Poor project performance is often attributed erroneously to PMs and SEs that must perform in an environment characterized by: Inadequate proposal preparation and analytical due diligence in understanding the user's problem space and operational needs. Unrealistic proposal assumptions and contract constraints – such as overly aggressive schedules and inadequate funding. A Source Selection Evaluation Process that is overshadowed by a highly competitive "Acquisition Game" of perceptions, influence, persuasion, and potential conflicts of interest. Project Management and Engineering "stovepipes" that limit understanding of each other's roles, accountabilities, and their respective contributions. Contract "requirements creep" by the Acquirer with an expectation or Developer accommodation without appropriate contract cost modification. Deficiencies in Engineering and Systems Engineering due to outdated educational and competency paradigms. As a result of unreasonable and unrealistic constraints by the "game" conditions, no one really wins ‐ the User, the Acquirer, the Developer, or supporting subcontractors and vendors. Indeed, upon contract award, the project conundrum becomes: "Good news! We won the contract … Bad news. We won the contract!" Project Managers and Systems Engineers are then burdened with the impossible task of achieving contract financial, technical, and schedule "stretch" objectives in which they may have had little opportunity for input. This paper explores each of these conditions, through illustrative examples from a range of business domains and industries perspectives, along with potential opportunities for improvement so that, fundamentally, the game itself is changed – changed to one that can be won.